PREEXISTING PATHOLOGY IN ZERO BIOPSIES DONOR KIDNEYS AND IN ONE-HOUR BIOPSIES OF KIDNEY ALLOGRAFTS - M. L. Arefjev; M. G. Minina; I. M. Iljinsky (Вестник трансплантологии и искусственных органов, 2011)
In the following paper we present thedetailed analisys of data available in the literature concerning the «zero» byopsies of donor kidneys and «hour» byopsies of kidney allografts. With attention we take a look on a previous existed pathology of cadaver kidneys discovered through byopsies. We trying to define the role of preexisting pathology in the following results of transplantation. Moreover we describe the histologic criteria of suitability of cadaver kidneys for transplantation